Martin Heidegger mengenai Mengada secara Otentik dan Relevansinya bagi Pelayanan Kesehatan - Jena, Yeremias (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2015)
Human existence is perceived by Martin Heidegger as Dasein, that being-in-the-world. The modes of existence of Dasein in the world are Being-with-the-other (Mitsein), Being-alongside-things (Sein-bei), and Being-one’s-self (Selbstein). For Heidegger, the ideal mode of existence of Dasein is Being-one’s-self (Selbstein). Only through this mode of being that Dasein forms its distinctiveness from other entities which are just being-within-the-world. As to the convenience of enjoying the objects of the world, idle talk or gossipping can cause Dasein to forget its authentic being. After describing the thoughts of Heidegger on the fall of Dasein into being unauthentic, this paper highlights the ontological awareness of the existence of Dasein towards death as an authentic mode of existence. At the end of this writing, I propose narration as a ‘tool’ to be used by health care providers in assisting the patient to affirm and accept illness experience as their modes of being.